Upaya Peningkatan Kompetensi Guru dalam Menyusun Rencana Pelaksanaan Pembelajaran Melalui Supervisi Akademik Kepala Sekolah Di SMAN 1 Lembah Melintang Kabupaten Pasaman Barat - Ali Arman (STKIP Pesisir Selatan, 2016)
Abstract Based on observations and the author supervision of a teacher in SMAN 1 Valley Crossing West Pasaman, it was found that the Teacher Competence in preparing the RPP is still low. The purpose of this study is to describe and obtain information about improving teacher competence in preparing the RPP through academic supervision of the school principal in SMAN 1 Valley Crossing Barat. Penelitian Pasaman of a school action research. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subjects consisted of 29 teachers, all teachers at SMAN 1 Valley Crossing West Pasaman who are teachers trained investigators. Data were collected by using observation sheet. Data were analyzed using percentages. Based on the research that has been done, it can be concluded that the academic supervision of the school head can improve teacher competence in formulating deploy Plan Learning in SMAN 1 Valley Crossing West Pasaman. It is seen from the readiness of teachers in the implementation of learning. Besides, based on the results penilitian conducted average value RPP made by teachers also undergo increase of the cycle of the average value of 50.19 and 80.75 in cycle two (good).Keywords: Competence Teachers, Prepare lesson plans, Academic Supervision